ANALISIS KETERAMPILAN CREW DALAM PENGGUNAAN APAR SEBAGAI UPAYA PENIGKATAN KESELAMATAN DI KMP SALVINO - Muliza, Rozaa; Mashartanto, Achmad Ali; Roselia, Fauziah; Baskoro, Bayu yudho; Abadi, Kurniawan (STKIP Subang, 2026)
This research focuses on crew skills in the use of fire extinguishers to improve safety at KMP Salvino, the purpose of this study is to analyze crew skills in the use of fire extinguishers, identify influencing factors, and make the necessary efforts to improve the ability and preparedness of the crew. This research is also useful for evaluating ship safety training and improving crew capabilities. This study uses a qualitative descriptive method, with informants selected through purposive sampling, namely Mualim III, Sailor I, and Sailor II. Data was obtained through interviews, observations, and documentation using interview sheet and observation sheet instruments. Data analysis is carried out through the process of data reduction, fishbone diagrams, data presentation, and drawing conclusions. The results of the study show that crew skills in the use of fire extinguishers are in the category of being quite good, but still need to be improved through more structured training, equitable practice, and strengthening understanding of fire types.